Diminish partially shaded PV array mismatch loss through SRA algorithm based TTCL reconfiguration method - Kumar, Arjun; Agarwal, Ruchi (Physica scripta, 2025)
Due to mismatch losses, partial shadow lowers a PV array’s output power. Therefore, choosing the right PV array configuration for optimal power generation is one of the most important variables to take into account. Unlike the traditional total-cross-tie (TCT) configuration, the triple-tied-cross-link (TTCL) layout has a less tied connection. The suggested Successive Ring Adder (SRA) method is used as a reconfiguration strategy to further improve the TTCL configuration’s performance. The PV modules are rearranged with the placement matrix generated by the proposed SRA algorithm using MATLAB coding. The conventional TTCL configuration is reconfigured by using the SRA algorithm. That results in the suggested successive ring adder algorithm-based triple tied cross link (SRAA-TTCL) configuration effectively dispersing the shading pattern to mitigate the partial shading effects. The suggested approach has been examined for use with both symmetrical (9 × 9) and asymmetrical (9 × 6) PV designs. The author examines the proposed techniques with shading group I to shading group VIII and evaluates the performance parameters Global Maximum Power (GMP), Fill Factor (FF), Mismatch Loss (ML), and Efficiency ( η ) compared with the results of SP and TTCL configurations and other puzzle-based techniques. As authors examine shading pattern group II, the suggested SRAA-TTCL enhances the performance parameter GMP (12.76%), FF(6.83%), and efficiency (1.47%) with reduction in ML(9.14%) as compared with the conventional TTCL configuration. The output characteristics, such as current–voltage (I-V) and power-voltage (P-V), are examined in each shading pattern case. The temperature variation case is also illustrated. All the analysis has been done in MATLAB 2021a.